A flexible, multi-faceted profession: Supporting frontline practitioners in the fight against COVID-19. (2nd May 2020) - Baldwin, Sharin; Kelly, Patricia
Abstract : Novel coronavirus was first identified in Wuhan City, China and was reported to the World Health Organization (WHO) in China on 31 December, 2019. On 30 January, WHO declared the outbreak of COVID-19 a 'public health emergency of international concern'. Since then, the virus has spread rapidly across the world, with the WHO declaring it a pandemic on 11 March 2020. This article describes a case study where two health visitors were able to adapt and use their wide-ranging skills to support frontline health professionals in acute settings to meet the demands placed on them during these unprecedented times.